HARGA OPSI CALL TIPE EROPA MENGGUNAKAN SIMULASI MONTE CARLO STANDAR DAN TEKNIK ANTITHETIC VARIATES - Qur’ani, Anisah Mardiah; Kasse, Irwan; Syata, Ilham (Jurnal MSA ( Matematika dan Statistika serta Aplikasinya), 2020)
The European call option is a contract that gives the contract holder the right to buy a certain asset at a price and a certain period of time, which is the execution time at maturity. This study aims to determine the accuracy of the simulation results of stock prices to determine the price of European call options from simulation of standardMonte Carlo and the antithetic variates technique using R-Studio software. The results of the simulation of the two methods will approach the option price of the analytic solution. Analytical solutions in this study use the Black-Scholes model to obtain a standard price that serves to compare the two methods. The call option price of the European type uses the Black-Scholes model as a benchmark is 14.20281. In the 1.000.000 th standard Monte Carlo simulation, the call option price converges to 14.69786 with a standard error of 0.019, while the 100.000 th Monte Carlo-antithetic variates produces a call option price converges at 14.69801 with a standard error of 0.043. The results of this study indicate that Monte Carlo simulation with antithetic variates technique is more accurate because it produces an option value faster to converge with a relatively smaller standard error